An Intelligent Customer Complaint Management System with Application to the Transport and Logistics Industry - Faed, Alireza (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2013)
This thesis addresses the issue of customer complaints in the context of Customer Relationship Management (CRM). Following a comprehensive survey of the current literature on CRM, it describes the development of a new intelligent CRM (I-CRM) framework, which integrates in a single approach different innovative analytical methods. Unlike conventional approaches, this new methodology can handle customer complaints with respect to different variables, thus allowing organizations to find their key customers and key complaints, and to address and provide solutions for their major complaints, hence promoting business development. The  thesis also describes the successful application of the method to a real-world  case: the virtually immeasurable number of complaints from truck drivers at the  port city Fremantle in Western Australia.